Exposure to Maternal Pre- and Postnatal Psychological Distress: Effects on Brain Structure in 5-year-old Children - Svensk, Amira (My University, 2023)
Background: Maternal distress is hypothesized to be an important contributor to child neurodevelopmental trajectories but relatively few studies have explored the effect of distress (i.e., prolonged stress/psychological strain) longitudinally. The aim of this study is to investigate associations between exposure to pre- and postnatal maternal distress at different developmental stages and child brain development at 5 years of age. Methods: Mother-child dyads (n = 173) were recruited from the FinnBrain longitudinal birth cohort. Maternal stress was assessed with a composite distress measure consisting of the Edinburgh Postnatal Depression Scale (EPDS) and the anxiety subscale of the Symptom Checklist-90-Revised (SCL) at six time points: prenatally at 14, 24 and 34 gestational weeks (gwks), and postnatally at 3, 6 and 24 months (i.e., 2 years). High-resolution T1-weighted structural images of participating 5-year-olds were obtained using a 3 Tesla magnetic resonance imaging (MRI) system. Data were analyzed through voxel-based morphometry (VBM) and partial correlation analyses. Results: The research findings uncovered notable, widespread, and partially enduring associations between maternal symptoms and offspring brain morphology. Higher prenatal stress at 14 gwks was positively associated with regional gray matter (GM) densities in the right superior parietal lobe and precuneus. In contrast, postnatal stress at 3 months was linked to negative associations with GM densities in motor areas (left supplementary motor cortex, left and right cerebellar regions including vermal lobules VIII–X), the left anterior insula, right superior frontal areas and supramarginal gyrus. Furthermore, postnatal stress at 6 months demonstrated a positive relationship with GM densities in the right calcarine and lingual gyri, while stress at 2 years of age was negatively associated with GM densities in the left supramarginal and right superior frontal gyri. Potential covariates were accounted for in all analyses. Conclusion: The present study contributes to the literature on the adverse effects of elevated maternal distress on developmental outcomes in offspring. Additionally, it provides support for hypotheses proposing that fetal and early life exposure to stress can influence the structural development of the brain.
Keywords: maternal distress, depression, anxiety, prenatal stress, postnatal stress, magnetic resonance imaging (MRI), structural brain development, voxel-based morphometry (VBM)